RETRACTED: Regulation of environmental safety of the Kyrgyz republic - Akmatova Amanai; Asanbekova Dzhamilia; Sadykova Altynai; Zholdoshbaiuulu Zamirbek; Toktorov Egemberdi (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001